An experimentally anchored map of transcriptional start sites in the model cyanobacterium Synechocystis sp. PCC6803 - Mitschke, Jan (National Academy of Sciences, 2011)
There has been an increasing interest in cyanobacteria because these photosynthetic organisms convert solar energy into biomass and because of their potential for the production of biofuels. However, the exploitation of cyanobacteria for bioengineering requires knowledge of their transcriptional organization. Using differential RNA sequencing, we have established a genome-wide map of 3,527 transcriptional start sites (TSS) of the model organism Synechocystis sp. PCC6803. One-third of all TSS were located upstream of an annotated gene; another third were on the reverse complementary strand of 866 genes, suggesting massive antisense transcription. Orphan TSS located in intergenic regions led us to predict 314 noncoding RNAs (ncRNAs). Complementary microarray-based RNA profiling verified a high number of noncoding transcripts and identified strong ncRNA regulations. Thus, ∼64% of all TSS give rise to antisense or ncRNAs in a genome that is to 87% protein coding. Our data enhance the information on promoters by a factor of 40, suggest the existence of additional small peptide-encoding mRNAs, and provide corrected 5′ annotations for many genes of this cyanobacterium. The global TSS map will facilitate the use of Synechocystis sp. PCC6803 as a model organism for further research on photosynthesis and energy research.